A Meta-Analysis of Country-of-Origin Effects - Peterson, Robert A.; Jolibert, Alain J. P. (Journal of International Business Studies, 1995)
This note reports a quantitative analysis of the country-of-origin (COO) effect. Based on fifty-two articles or papers containing sixty-nine independent studies and 1,520 effect sizes, an analysis of fifteen study characteristics revealed that country-of-origin effects are only somewhat generalizable. Using omega-squared as the measure of effect size, verbal product descriptions produced larger COO effect sizes than did the presence of an actual product. Likewise, single-cue studies produced larger COO effect sizes than did multiple-cue studies, and larger samples produced effect sizes that on average were greater than those produced by smaller samples. The size of an observed COO effect was a function of whether the dependent variables was a quality/reliability perception or a purchase intention; the average effect size of quality/reliability perceptions was .30, whereas the average effect size for purchase intentions was .19. Purchase intentions were most susceptible to methodological artifacts than were quality/reliability perceptions. Study findings selectively confirm and refute common beliefs regarding the impact of a country-of-origin cue on product perceptions and purchase intentions.